Negative cooperativity across 1-adrenoceptor homodimers provides insights into the nature of the secondary low-affinity CGP 12177 1-adrenoceptor binding conformation - Gherbi, Karolina; May, Lauren T.; Baker, Jillian G.; Briddon, Stephen J.; Hill, Stephen J. (Federation of American Society of Experimental Biology, 2015)
At the β1-adrenoceptor, CGP 12177 potently antagonizes agonist responses at the primary high-affinity catecholamine conformation while also exerting agonist effects of its own through a secondary low-affinity conformation. A recent mutagenesis study identified transmembrane region (TM)4 of the β1-adrenoceptor as key for this low-affinity conformation. Others suggested that TM4 has a role in β1-adrenoceptor oligomerization. Here, assessment of the dissociation rate of a fluorescent analog of CGP 12177 [bordifluoropyrromethane-tetramethylrhodamine-(±)CGP 12177 (BODIPY-TMR-CGP)] at the human β1-adrenoceptor expressed in Chinese hamster ovary cells revealed negative cooperative interactions between 2 distinct β1-adrenoceptor conformations. The dissociation rate of 3 nM BODIPY-TMR-CGP was 0.09 ± 0.01 min−1 in the absence of competitor ligands, and this was enhanced 2.2- and 2.1-fold in the presence of 1 µM CGP 12177 and 1 µM propranolol, respectively. These effects on the BODIPY-TMR-CGP dissociation rate were markedly enhanced in β1-adrenoceptor homodimers constrained by bimolecular fluorescence complementation (9.8- and 9.9-fold for 1 µM CGP 12177 and 1 µM propranolol, respectively) and abolished in β1-adrenoceptors containing TM4 mutations vital for the second conformation pharmacology. This study suggests that negative cooperativity across a β1-adrenoceptor homodimer may be responsible for generating the low-affinity pharmacology of the secondary β1-adrenoceptor conformation